New species and records of Copris (Coleoptera: Scarabaeidae; Scarabaeinae) from Central America - Kohlmann, Bert; Cano, Enio; Delgado, Leonardo (Zootaxa, 2003)
Two new species of Copris Geoffroy from Guatemala and Honduras are described and illustrated: Copris caliginosus sp. nov. and Copris nubilosus sp. nov. Both species are related to C. sallei Harold, which is redescribed and illustrated for the first time. A key for the remotus complex is also included. New distributional records of Copris are provided for five species and subspecies from Guatemala and El Salvador.